Design and analysis of a three-phase interleaved DC-DC converter - Huang, Huizhen (2019)
Recently, next-generation electrical grid, smart grid has drawn much attention in both academia and industry. The high-level utilization of renewable resources and energy storage system in smart grid challenges conventional converter topologies and calls for bidirectional converters. As a result, a multi-phase DC-DC interleaved converter that allows bidirectional power flow has been developed. Another feature of the interleaved DC-DC converter is the reduction of the current ripple, which is achieved by proper phase-shifting. In this dissertation, a three-phase interleaved DC-DC converter is designed and analyzed for microgrid application. This converter topology is derived from traditional single-phase boost converter. All parameters design and components selection are presented. Dual-loop control design for voltage regulation mode (VRM) is introduced as well. The proposed design is implemented using the software simulations and is compared with the results that were obtained experimentally.